A Cognitive Approach to Teaching Pronunciation through Tongue Twisters - Maria Monika Balinayan; Nurteteng (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study examines the effectiveness of a cognitive approach in teaching pronunciation through tongue twisters among seventh-grade students at SMPTK Diaspora, Sorong. Indonesian EFL learners often face pronunciation problems caused by first language interference and limited exposure to authentic English sounds. Previous studies have shown that tongue twisters improve pronunciation accuracy, but few have explored how they support pronunciation from a cognitive perspective. This research aims to determine whether tongue twisters can enhance students’ pronunciation by engaging attention, memory, and self-monitoring processes. A pre-experimental design with a one-group pretest–posttest model was employed. The participants were 26 seventh-grade students selected from a total population of 37. Data were collected through pronunciation tests administered before and after treatment and analyzed using the Paired Sample T-test in SPSS 20. The results showed a significant improvement in students’ pronunciation scores, with the mean rising from 46.92 in the pretest to 65.88 in the posttest (p = 0.001 < 0.05). This indicates that tongue twister practice had a positive effect on pronunciation performance. The findings suggest that tongue twisters help learners internalize correct sound patterns by promoting focused attention, memory activation, and articulatory awareness. Applying a cognitive approach through tongue twisters effectively improves students’ pronunciation and creates an engaging learning experience. This study contributes to pronunciation pedagogy by linking cognitive theory with classroom practice and offers practical insights for teachers in similar EFL contexts.